Benefit and costs of surveillance on cancer risk patients: the example of pancreatic cystic tumors. (30th September 2020) - Cortesi, P A; Tamburino, D; Facchetti, R; Micale, M; Mantovani, L G; Crippa, S; Capurso, G
Abstract: Background: Increasing number of expert recommendations and guidelines of cancer surveillance have become available in the last decade. This complex scenario have increased the uncertainty on the most valuable approach to adopt. This study aim to evaluate the case of premalignant pancreatic primarily cystic tumors surveillance, assessing the differences of programmes proposed and applied. Methods: A review of American, European and International guidelines for surveillance of asymptomatic neoplastic pancreatic cysts was performed to assess the difference of programmes proposed. An amibispective observational study, form 1995 to 2019, was conducted on patients with premalignant pancreatic primarily cystic tumors monitored in 10 centers from 4 European countries. We estimated incidence of pancreatic cancer and surgery intervention for high grade dysplasia (HGD)/Pancreatic cancer. We also assessed the follow-up visits and exams frequency during the surveillance period and the relative mean cost per patient-year. Results: The guidelines reported significant differences in patient's stratification, surveillance intensity (frequency of visits-exams), and surveillance duration. In the study conducted, 961 patients were enrolled with a median (IQR) follow-up of 4.47(2.8-7.0) years. HGD or Pancreatic carcinoma was reported by 43(4.4%) patients and 67(7.0%) undergone pancreatic surgery. Within the pancreatic surgery performed, 60.6% was rated as over-treated (None/low-moderate grade dysplsya). A big variability was reported in the surveillance with a median (IQR) visit per patient-year of 0.77(0.49-1.03) and with a mean cost per-patient year of €163.3. Conclusions: Significant heterogeneity between surveillance approaches was reported in guidelines and clinical practice. Reliable and specific data on efficacy and costs associated to surveillances programmes proposed are needed in order to perform robust assessment and help decision makers in implementing the most valuable one. Key messages: Significant variability of surveillance programmes proposed and applied for pancreatic cystic are reported in the guidelines and clinical practice. We need more robust efficacy and costs data in order to identify the most valuable surveillances approach to implement in clinical practice and recommend in the national and international guidelines.